Effects of foam roller on pain intensity in individuals with chronic and acute musculoskeletal pain: a systematic review of randomized trials - Inaê Silva Santos; Almir Vieira Dibai-Filho; Patrícia Gabrielle dos Santos; José Djalma Arrais Júnior; Daniella Dias de Oliveira; Daniel Santos Rocha; Cid André Fidelis-de-Paula-Gomes (BMC Musculoskeletal Disorders, 2024)
Abstract Objective To analyze the effects of using foam roller on pain intensity in individuals with chronic and acute musculoskeletal pain. Methods This systematic review was registered in the National Institute for Health Research’s prospective online registry of systematic reviews (PROSPERO) under CRD42023456841. The databases Pubmed, Medline (via Ovid), Embase, BVS, and PEDro (Physiotherapy Evidence Database) were consulted to carry out this systematic review. Notably, the records of clinical trials characterized as eligible were manually searched. The search terms were: (foam rolling OR foam rolling vibration) AND (acute musculoskeletal pain) AND (chronic musculoskeletal pain). The search was performed until August 22, 2023. For the analysis of the methodological quality, the PEDro scale was used for each of the manuscripts included in the systematic review. Due to the heterogeneity in the studies included in this systematic review, performing a meta-analysis of the analyzed variables was impossible. Results Only six manuscripts were eligible for data analysis. The type of FR used was non-vibrational, being applied by a therapist in only one of the manuscripts. With an application time ranging from at least 45 s to 15 min, the non-vibrational FR was applied within a day up to six weeks. Using the PEDro scale, scores were assigned that varied between 4 and 8 points, with an average of 6 ± 1.29 points. Only two randomized clinical trials found a significant benefit in pain intensity of adding FR associated with a therapeutic exercise protocol in individuals with patellofemoral pain syndrome and chronic neck pain. Conclusion The results of this systematic review do not elucidate or reinforce the clinical use of FR in pain intensity in individuals with chronic and acute musculoskeletal pain.